COSMO-RS screening of organic mixtures for membrane extraction of aromatic amines: TOPO-based mixtures as promising solvents - Gilles Van Eygen; Catherine Echezuria; Anita Buekenhoudt; João A.P. Coutinho; Bart Van der Bruggen; Patricia Luis (Green Chemical Engineering)
Aromatic amines are crucial in pharmaceuticals, but their synthesis is challenging due to unfavorable reaction equilibria and the use of costly, environmentally unfriendly methods. This study presents a membrane extraction (ME) process for in situ product removal (ISPR) of aromatic amines. Using a supported liquid membrane (SLM), α-methylbenzylamine (MBA) and 1-methyl-3-phenylpropylamine (MPPA) were separated from isopropyl amine (IPA). Conductor-like Screening Model for Real Solvents (COSMO-RS) was employed to screen over 200 organic mixtures, identifying twelve mixtures based on trioctylphosphine oxide (TOPO), lidocaine, and menthol as solvent candidates, due to their hydrophobicity. These mixtures were analysed for critical solvent properties including density, viscosity, hydrophobicity, and H-bonding interactions. ME tests showed TOPO-thymol had the highest solvent residual and selectivity. Moreover, TOPO-thymol demonstrated solute fluxes of 9.0±3.0 g/(m2 h) for MBA, 16.5±5.4 g/(m2 h) for MPPA, and 0.7±0.3 g/(m2 h) for IPA, with selectivity values of 12.4±0.8 for MBA/IPA and 22.8±1.4 for MPPA/IPA. Compared to undecane, which had lower selectivity values of 6.9±0.8 for MBA/IPA and 10.1±1.3 for MPPA/IPA, TOPO-thymol showed superior selectivity, indicating its promise as an extractant for ME applications.